2018
DOI: 10.30964/auebfd.405014
|View full text |Cite
|
Sign up to set email alerts
|

Dezavantajlı Öğrencilerin Fen Okuryazarlık Performanslarının Duyuşsal Özellikleriyle İlişkisinin İncelenmesi

Abstract: Bu araştırmada PISA 2015 kapsamında dezavantajlı öğrencilerin karakteristik özellikleri ile ilgili hangi değişkenlerin fen performanslarını anlamlı bir şekilde yordadığı incelenmiştir. Araştırma kapsamında PISA 2015 uygulamasından elde edilen Türkiye verileri kullanılmıştır. Araştırmada bağımlı değişken olarak PISA 2015 uygulamasında her bir öğrenci için hesaplanmış olan 10 farklı olası başarı puanı (plausible values), bağımsız değişken olarak ise öğrencilerin fen öğrenme motivasyonları, fen konularına ilgiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…When the variables in the model were examined, it was determined that the variables of instrumental motivation and hinderance in learning science learning did not significantly predict scientific literacy. Yetişir et al (2018) found similar results with the results of this research in their study, as they examined the effect of instrumental motivation on scientific literacy. However, in the study conducted by OECD (2016), it was concluded that instrumental motivation was a significant predictor of scientific literacy.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 85%
See 1 more Smart Citation
“…When the variables in the model were examined, it was determined that the variables of instrumental motivation and hinderance in learning science learning did not significantly predict scientific literacy. Yetişir et al (2018) found similar results with the results of this research in their study, as they examined the effect of instrumental motivation on scientific literacy. However, in the study conducted by OECD (2016), it was concluded that instrumental motivation was a significant predictor of scientific literacy.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 85%
“…In the report published by OECD (2016), it was stated that this variable had an indirect effect on science performance. Moreover, Yetişir et al (2018) also concluded that the variable had a positive effect. Therefore, it is recommended that students are provided with learning environments in which they have the opportunity to enjoy, be content, and actively participate in learning science.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 98%
“…Alanyazın incelendiğinde Türkiye'de PISA araştırmaları ile ilgili nicel ve nitel olmak üzere çok sayıda çeşitli araştırmanın yapıldığı tespit edilmiştir (Altun & Akkaya, 2014;Aydoğdu-İskenderoğlu & Baki, 2011;Aydoğdu-İskenderoğlu, Erkan & Serbest, 2013;Bahadır, 2012;Başusta & Gelbal, 2015;Batur & Ulutaş, 2013;Berberoğlu, 2007;Berberoğlu & Kalender, 2005;Bozkurt, 2016;Bozkurt, Uzun & Lee, 2015;Çobanoğlu & Kasapoğlu, 2010;Demir & Kılıç, 2010;Döş & Atalmış, 2016;Duru & Korkmaz, 2010;Güler, 2013;İlgün Dibek, Yavuz & Çokluk Bökeoğlu, 2018;İş, 2003;Kabael & Barak, 2016;Mutluer & Büyükkıdık, 2017;Okur, 2008;Özberk, Atalay Kabasakal & Boztunç Öztürk, 2017;Savran, 2004;Taşdelen Teker, Boztunç Öztürk & Eroğlu, 2014;Yavuz & Çetin, 2017;Yetişir, Batı, Kahyaoğlu & Birel, 2018;Yıldırım, 2009;Yıldırım, Şahin & Sezer, 2017;Yılmaz Fındık & Kavak, 2017;Yolsal, 2016). Bu araştırmaların çoğunluğunda nicel araştırma yöntemi kullanılarak çalışmalar yapılırken (Başusta & Gelbal, 2015;Berberoğlu, 2007;Berberoğlu & Kalender, 2005;Demir & Kılıç, 2010;Döş & Atalmış, 2016;İlgün Dibek, vd., 2018;İş, 2003 2017; Özberk, vd., 2017;…”
Section: Introductionunclassified